2006
DOI: 10.1074/jbc.m513516200
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Is Required for Normal Osteoclast Function and Is Down-regulated by Calcitonin

Abstract: Osteoclast motility is thought to depend on rapid podosome assembly and disassembly. Both -calpain and m-calpain, which promote the formation and disassembly of focal adhesions, were observed in the podosome belt of osteoclasts. Calpain inhibitors disrupted the podosome belt, blocked the constitutive cleavage of the calpain substrates filamin A, talin, and Pyk2, which are enriched in the podosome belt, induced osteoclast retraction, and reduced osteoclast motility and bone resorption. The motility and resorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 89 publications
(106 reference statements)
4
51
1
Order By: Relevance
“…Our study shows that -calpain is crucial for NO-induced osteoclast motility and that -calpain is regulated by a Ca 2+ signal that requires PKG1, Src and VASP. Our findings are consistent with results from previous studies showing calpain activity in osteoclasts (Lee et al, 2005;Hayashi et al, 2005;Marzia et al, 2006). Earlier research suggested calpain involvement in osteoclast differentiation and function (Lee et al, 2005;Marzia et al, 2006), but here we describe for the first time -calpain activation and Ca 2+ signaling in NO/cGMP-induced osteoclast motility.…”
Section: Discussionsupporting
confidence: 83%
“…Our study shows that -calpain is crucial for NO-induced osteoclast motility and that -calpain is regulated by a Ca 2+ signal that requires PKG1, Src and VASP. Our findings are consistent with results from previous studies showing calpain activity in osteoclasts (Lee et al, 2005;Hayashi et al, 2005;Marzia et al, 2006). Earlier research suggested calpain involvement in osteoclast differentiation and function (Lee et al, 2005;Marzia et al, 2006), but here we describe for the first time -calpain activation and Ca 2+ signaling in NO/cGMP-induced osteoclast motility.…”
Section: Discussionsupporting
confidence: 83%
“…Many proteins critical for podosome organization are regulated by calcium. For example, Pyk2 can be 14 activated by calcium (Sanjay et al, 2001) and calpains are Ca2+-dependent proteases critical for osteoclasts function (Marzia et al, 2006) that may cleave 3 integrin (Flevaris et al, 2007), RhoA (Kulkarni et al, 2002), Pyk2 (Marzia et al, 2006) and WASp (de la Fuente et al, 2007). Change in calcium concentration affects podosome organization of osteoclast (Miyauchi et al, 1990) and knocking out the calcium transporter TRPV5 generates inactive osteoclasts (van der Eedern et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, WASp-deficient osteoclasts on bone showed a decrease in the area of bone surface resorbed, whereas other parameters, such as volume and depth of resorption pits, were unaffected. In addition, calpain, which can proteolyze the podosome proteins talin, Pyk2 and filamin, has been found to be important for osteoclast activity (Marzia et al, 2006). Dynamin localizes to osteoclast podosomes, and expression of dynamin mutants can inhibit osteoclast activity (Bruzzaniti et al, 2005).…”
Section: Discussionmentioning
confidence: 99%